2018
DOI: 10.1051/0004-6361/201732106
|View full text |Cite
|
Sign up to set email alerts
|

PSR B0943+10: low-frequency study of subpulse periodicity in the Bright mode with LOFAR

Abstract: We use broadband sensitive LOFAR observations in the 25-80 MHz frequency range to study the single-pulse emission properties of the mode-switching pulsar B0943+10. We review the derivation of magnetospheric geometry, originally based on low-frequency radio data, and show that the geometry is less strongly constrained than previously thought. This may be used to help explain the large fractional amplitudes of the observed thermal X-ray pulsations from the polar cap, which contradicted the almost aligned rotator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In conclusion, the angle between magnetic and spin axis derived by Bilous (2018) is constrained in the range: 5 • < ξ < 30 • . For each value of ξ only two well defined values of χ are possible and are in the ranges 3 • < χ < 22 • (inside traverse model) or 7 • < χ < 38 • (outside traverse model).…”
Section: Geometry From Radio Datamentioning
confidence: 88%
See 3 more Smart Citations
“…In conclusion, the angle between magnetic and spin axis derived by Bilous (2018) is constrained in the range: 5 • < ξ < 30 • . For each value of ξ only two well defined values of χ are possible and are in the ranges 3 • < χ < 22 • (inside traverse model) or 7 • < χ < 38 • (outside traverse model).…”
Section: Geometry From Radio Datamentioning
confidence: 88%
“…In addition, thanks to the increased counting statistics, we showed that the single blackbody fit to the B-mode emission, that was consistent with the 2014 data, is actually disfavored. However, if we adopt the pulsar geometrical configuration derived from recent radio studies (Bilous 2018), these simple models face two problems: a) they can not give rise to the significant and energy-dependent pulsed fraction observed in the Q-mode; b) they can not correctly reproduce the spectrum of the unpulsed flux, that should be dominated by the blackbody emission, while it can be fitted well by a single power law.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the line of sight passes through the emission region, drifting subpulses can be seen. The carousel model was successful in interpreting subpulse drifting behaviour of many pulsars (Bhattacharyya et al 2007;Rankin et al 2013;Rankin & Rosen 2014;Bilous 2018). In the original carousel model, the drift rate remains constant, and thus it is difficult to explain the observed multiple drift modes in a pulsar based on the original carousel model.…”
Section: Discussionmentioning
confidence: 99%